2009
DOI: 10.1074/jbc.m109.014829
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Acyl Intermediates of the Plasmodium falciparum Fatty Acid Synthesis Pathway

Abstract: Acyl carrier protein (ACP) plays a central role in fatty acid biosynthesis. However, the molecular machinery that mediates its function is not yet fully understood. Therefore, structural studies were carried out on the acyl-ACP intermediates of Plasmodium falciparum using NMR as a spectroscopic probe. Chemical shift perturbation studies put forth a new picture of the interaction of ACP molecule with the acyl chain, namely, the hydrophobic core can protect up to 12 carbon units, and additional carbons protrude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 43 publications
5
38
0
2
Order By: Relevance
“…Instead, the cavity observed in the VhACP A75H structure matches subpocket II of ACP that was recently described in molecular dynamics simulations (32). Evidence of subpocket II was also provided by NMR studies of P. falciparum ACP, and it appears likely that the acyl chains spend time in both subpockets in vivo (32,39). Further experiments are needed to determine how this influences acyl chain binding and whether potential inhibitors can be optimized based on the binding to both subcavities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the cavity observed in the VhACP A75H structure matches subpocket II of ACP that was recently described in molecular dynamics simulations (32). Evidence of subpocket II was also provided by NMR studies of P. falciparum ACP, and it appears likely that the acyl chains spend time in both subpockets in vivo (32,39). Further experiments are needed to determine how this influences acyl chain binding and whether potential inhibitors can be optimized based on the binding to both subcavities.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not unexpected that the divalent cation binding affinity is different in apo-, holo-, and acyl-ACP (18,34). It has recently been suggested that the electrostatic repulsion between helices II and III of P. falciparum ACP is important for the prompt opening and extraction of the acyl chain (39). Therefore, divalent cation binding will likely affect this process by diminishing the repulsive forces between the two helices (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The function of PfACP has been demonstrated by complementation [129] and recombinant expression in E. coli [65,67], and also through its ability to support FASII enzymes in vitro [65,66]. There have been several structural studies of PfACP [130][131][132][133] and a considerable amount is known about the carrier's conformation, stability and redox state in bloodstage parasites. Intriguingly, PfACP has also been found to possess enzymatic activity, catalyzing both self-acylation and malonyl-transferase reactions in vitro [68,69].…”
Section: Acyl-carrier Protein (Acp)mentioning
confidence: 99%
“…Cloning, overexpression and purification of 15 N-labeled PfACP Proteins were expressed by cloning, overexpression and purification of P. falciparum holo and acyl-ACPs in E. coli as described (Upadhyay et al 2009 Inova 500, installed at the National Institute of Immunology, New Delhi, India, equipped with a triple resonance, Z pulsed field gradient probe. Experiments were performed at 300 K. NMR data was processed on a workstation running Red Hat Enterprize Linux 5.0, using NMRPipe/NMRDraw (Delaglio et al 1995) and analyzed using Sparky (Goddard and Kneller 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In most of the acyl-ACP intermediates (with the exception of rat), the hydrophobic core increases in size to accommodate the growing acyl chain. The molecular basis of ACP expansion upon acyl chain insertion has recently been disclosed by our NMR studies on P. falciparum acyl-ACP intermediates (Upadhyay et al 2009), where the electrostatic repulsion in conjunction with thrust due to the growing acyl chain favors expansion of the hydrophobic core of the ACP , resulting in large chemical shift changes. In this paper, we report the backbone chemical shift assignments of the acyl-ACPs of P. falciparum viz.…”
Section: Introductionmentioning
confidence: 98%